2021
DOI: 10.5194/wes-6-131-2021
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of intra-hourly wind power ramps at the wind farm scale and associated processes

Abstract: Abstract. One of the main factors contributing to wind power forecast inaccuracies is the occurrence of large changes in wind power output over a short amount of time, also called “ramp events”. In this paper, we assess the behaviour and causality of 1183 ramp events at a large wind farm site located in Victoria (southeast Australia). We address the relative importance of primary engineering and meteorological processes inducing ramps through an automatic ramp categorisation scheme. Ramp features such as ramp … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…As persistence inherently performs well over stationary wind regimes, lower %Imp P with easterlies was expected. Note the prevalence of westerly ramps was associated with mesoscale and synoptic-scale frontal systems characteristic of southeast Australia [70]. The considerations above underline the potentially critical role of terrain roughness, topography and synoptic-scale meteorology, adding another layer of complexity to short-term forecasting.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As persistence inherently performs well over stationary wind regimes, lower %Imp P with easterlies was expected. Note the prevalence of westerly ramps was associated with mesoscale and synoptic-scale frontal systems characteristic of southeast Australia [70]. The considerations above underline the potentially critical role of terrain roughness, topography and synoptic-scale meteorology, adding another layer of complexity to short-term forecasting.…”
Section: Resultsmentioning
confidence: 97%
“…We further evaluated the performance of the forecasts independently during wind power ramps, i.e., when large forecast errors were likely to occur. The ramp identification approach followed that of a previous study at the site focusing on ramp characterisation [70], where ramps were identified as the 1% strongest variations of the wind power time series based on continuous wavelet analysis. Further details about the ramp characterisation can be found in [70].…”
Section: Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the occurrence of wind power ramps seems to be associated with modest wind speeds when wind turbines are operating at below rated power in the steepest part of the power curve. Another factor which could affect the prevalence of ramp events is the passage of fronts [40] which is not picked up from the pressure fields alone although the individual charts in Figure 5 shows that such activity is frequently present for several of the most commonly occurring patterns. Alternatively, the transition between particular patterns may play a role and this is explored in the next section.…”
Section: Wind Power Rampsmentioning
confidence: 99%
“…Intermittent and abrupt changes in wind speed pose a risk to grid stability, especially during periods of low generation when there is limited availability of reserve power [3]. Curtailment of wind ramps represents a loss of potential profits and a possible increase in energy prices [4].…”
Section: Introductionmentioning
confidence: 99%